Research of neutron-physical characteristics of the Subcritical Nuclear Facility "Neutron Source” of NSC KIPT during the physical start-up - Karnaukhov, I.M.; Bezditko, O.P.; Borts, B.V.; Bykhun, O.V.; Bykov, V.T.; Gladkikh, P.I.; Glushchenko, L.I.; Gordienko, O.M.; Grevtsev V.G.; Karnaukhov I.I.; Krapiva, D.A.; Lutsenko, Ye.V.; et al. (Доповіді НАН України, 2024)
National Science Center “Kharkov Institute of Physics and Technology” jointly with the Argonne National Laboratory developed, designed and constructed the Subcritical Nuclear Facility “Neutron source based on the subcritical assembly driven by electron linear accelerator”. The article presents the main results obtained during the physical start-up of the plant, the program of which involved the staged loading of fuel assemblies into the core with subsequent measurements of its neutron-physical characteristics. In total, 37 fuel assemblies of WWR-M2 type were loaded into the facility core. The values o f the effective neutron multiplication factor keff and reactivity ρ of the subcritical assembly were measured after each loading step using the multiplication and area ratio methods. In addition, the neutron flux to electron current ratio method was tested for on-line reactivity monitoring. The investigations were performed when the accelerator was operated with 100 MeV electron beam energy, 2.7 μs electron pulse duration, 20 Hz pulse repetition rate and ≤ 40 mA beam pulse current. The obtained results were analyzed in terms of ensuring the facility nuclear safety at the next stage of its commissioning which is the pilot operation.